Genetic Variation in the SLC8A1 Calcium Signaling Pathway Is Associated With Susceptibility to Kawasaki Disease and Coronary Artery Abnormalities. (December 2016) - Shimizu, Chisato; Eleftherohorinou, Hariklia; Wright, Victoria J.; Kim, Jihoon; Alphonse, Martin P.; Perry, James C.; Cimaz, Rolando; Burgner, David; Dahdah, Nagib; Hoang, Long T.; Khor, Chiea Chuen; Salgado, Andrea; et al.
Abstract : Background—: Kawasaki disease (KD) is an acute pediatric vasculitis in which host genetics influence both susceptibility to KD and the formation of coronary artery aneurysms. Variants discovered by genome-wide association studies and linkage studies only partially explain the influence of genetics on KD susceptibility. Methods and Results—: To search for additional functional genetic variation, we performed pathway and gene stability analysis on a genome-wide association study data set. Pathway analysis using European genome-wide association study data identified 100 significantly associated pathways ( P <5×10 − 4 ). Gene stability selection identified 116 single nucleotide polymorphisms in 26 genes that were responsible for driving the pathway associations, and gene ontology analysis demonstrated enrichment for calcium transport ( P =1.05×10 − 4 ). Three single nucleotide polymorphisms in solute carrier family 8, member 1 ( SLC8A1 ), a sodium/calcium exchanger encoding NCX1, were validated in an independent Japanese genome-wide association study data set (meta-analysis P =0.0001). Patients homozygous for the A (risk) allele of rs13017968 had higher rates of coronary artery abnormalities ( P =0.029). NCX1, the protein encoded by SLC8A1, was expressed in spindle-shaped and inflammatory cells in the aneurysm wall. Increased intracellular calcium mobilization was observed in B cell lines from healthy controls carrying the risk allele. Conclusions—: Pathway-based association analysis followed by gene stability selection proved to be a valuable tool for identifying risk alleles in a rare disease with complex genetics. The role of SLC8A1 polymorphisms in altering calcium flux in cells that mediate coronary artery damage in KD suggests that this pathway may be a therapeutic target and supports the study of calcineurin inhibitors in acute KD. Abstract : Supplemental Digital Content is available in the text.